If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 10q = 6 + 9q Solving 3 + 10q = 6 + 9q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-9q' to each side of the equation. 3 + 10q + -9q = 6 + 9q + -9q Combine like terms: 10q + -9q = 1q 3 + 1q = 6 + 9q + -9q Combine like terms: 9q + -9q = 0 3 + 1q = 6 + 0 3 + 1q = 6 Add '-3' to each side of the equation. 3 + -3 + 1q = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 1q = 6 + -3 1q = 6 + -3 Combine like terms: 6 + -3 = 3 1q = 3 Divide each side by '1'. q = 3 Simplifying q = 3
| 3/4z=-5+1/2 | | 19.03+11.2y=5.1y-17.59-9.13 | | 4(-6x+1)=20-8x | | 335=5x^3 | | 8x+5-2x=-(5x-x) | | 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h | | 15.7g+18.66+7.2g=19.5g-13.64 | | -3(5a+6)=-5a+22 | | 0.7x-0.1=0.6x+2 | | 15x=2(1+9x) | | 2/3x=44 | | (5/9x)-(1/3)=3 | | -6r+1=-7r+20 | | 30+3x=-(3x+6) | | 3(x-4)=4x+1 | | -7-9k=7-7k | | =2z^2+13z+15 | | (2/3x)+(4/3)=(-4/3) | | 3(x-2)=4x-2-2x+3 | | 3(2x-x)=18-1 | | 8-9x-2=-40+6x-14 | | -28-6y=2(-6y+1) | | x^2/5=32 | | y+(y-50)=180 | | =4v*3v^4u^6*2u^7 | | -4x-13=6x+17 | | 3+c+6= | | 9+4x=3(x+4) | | 4-6m=(3m+14)-2(3m+5) | | 1.2t+3.4=-1.0 |